Sexual health communication between cancer survivors and providers: how frequently does it occur and which providers are preferred?. Issue 9 (22nd December 2014) - Sporn, Nora J.; Smith, Kelly B.; Pirl, William F.; Lennes, Inga T.; Hyland, Kelly A.; Park, Elyse R.
Abstract Background Sexual health concerns in cancer survivors are often unaddressed by providers. Study objectives were to assess cancer survivors' reported rates of communication with oncology providers about sexual health, preference for such communication with their oncology or primary care providers (PCPs), and factors associated with these communication rates and preferences. Methods Sixty‐six patients attending a cancer survivorship clinic were asked how often their oncologist addressed and initiated discussion about sexual functioning and whether they wanted their oncologist or PCP to ask about their sexual health. We also assessed whether various sociodemographic characteristics and levels of depression, anxiety, and sexual satisfaction were associated with survivors' sexual health communication rates and preferences. Results 41% of patients wanted their oncologist to ask about sexual health and 58% of patients wanted their PCP to ask about sexual health. Over 90% of patients reported that their oncologist infrequently addressed sexual health concerns and that their oncologist was unlikely to initiate such discussions. Education level influenced whether patients wanted their oncologist to ask about sexual health. Age, education level, and insurance type influenced whether patients wanted their PCP to ask about sexual health. Levels of depression, anxiety, and sexual satisfaction were not associated with communication rates or preferences. Conclusions Patients attending a survivorship clinic reported infrequent communication about sexual health with their oncology providers, despite wanting their providers to ask about sexual health concerns. Copyright © 2014 John Wiley & Sons, Ltd.